Komunikasi Pemasaran Rusunawa Kayu Putih Medan dalam Meningkatkan Daya Tarik Penyewa - Muzhirah; Muhammad Alfikri (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Rusunawa Kayu Putih Medan is one of the housing solutions for low-income people (MBR) in Medan City. However, the occupancy rate of Rusunawa Kayu Putih is still relatively low. This research aims to analyze marketing communications in increasing the attractiveness of tenants at Rusunawa Kayu Putih Medan. Data was collected through interviews with informants in the Rusunawa and analyzed to evaluate the effectiveness of the marketing communication strategy used by the Rusunawa. The results of this research indicate that marketing communications have a significant impact in increasing tenant attraction. By understanding the market characteristics and needs of prospective residents, as well as adopting appropriate communication strategies, it is hoped that the results of this research can create better awareness and greater interest in this residence, so that it can provide maximum benefits for urban communities in need.